GEOMETRIA DAS ABELHAS – ENSINANDO GEOMETRIA ATRAVÉS DE OBJETOS DE APRENDIZAGEM - ALBRECHT, ADÍLSON; PEREIRA, JULIANE S.; MOURA, LUÍS B. D.; WASTOWSKI, MARCELO V.; DILL, MARTIN A. A.; VARGAS, MÁRCIO R.; PEREIRA, TÂNIA M. (Salão do Conhecimento, 2013)
Resumo